Photonic nanojet assisted enhancement in transmission of light through hollow pyramid shaped near field probes. (16th April 2015) - Patel, H S; Kushwaha, P K; Swami, M K; Gupta, P K
Abstract: We report the use of sub-wavelength confinement of light using dielectric microspheres for enhancing transmission through the cantilever-based hollow probes used in a near-field scanning optical microscope. With an appropriate choice of the dielectric microsphere, an order of magnitude enhancement was achieved in transmission through the probe. In addition, transmission through such a tip was also found to be less sensitive to the axial and lateral offset between the beam waist and symmetry axis of the probe tip.